2004
DOI: 10.1007/s00203-003-0643-3
|View full text |Cite
|
Sign up to set email alerts
|

Subcellular localization of aflatoxin biosynthetic enzymes Nor-1, Ver-1, and OmtA in time-dependent fractionated colonies of Aspergillus parasiticus

Abstract: The biosynthesis of aflatoxin in Aspergillus parasiticus is a complex process that involves the activities of at least 18 pathway enzymes. The distribution of these enzymes within fungal colonies and fungal cells is not clearly understood. The objective of this study was to investigate the distribution and subcellular location of Nor-1, Ver-1, and OmtA, which represent early, middle, and late enzymatic activities, respectively, in the aflatoxin biosynthetic pathway. The distribution of these three enzymes with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
40
2
1

Year Published

2004
2004
2014
2014

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 42 publications
(46 citation statements)
references
References 35 publications
3
40
2
1
Order By: Relevance
“…Our current analysis indicates a linear correlation (R 2 = 0.855) between the function of the gpd promoter driving expression of the gfp gene and aflatoxin production. We are currently in the process of evaluating other strains of A. flavus transformed with gfp driven by aflatoxin gene promoters such as omtA or ver-1 [30,31] so that aflatoxin levels can be directly correlated to GFP values. …”
Section: Discussionmentioning
confidence: 99%
“…Our current analysis indicates a linear correlation (R 2 = 0.855) between the function of the gpd promoter driving expression of the gfp gene and aflatoxin production. We are currently in the process of evaluating other strains of A. flavus transformed with gfp driven by aflatoxin gene promoters such as omtA or ver-1 [30,31] so that aflatoxin levels can be directly correlated to GFP values. …”
Section: Discussionmentioning
confidence: 99%
“…The strains used in this study are listed in Table 1 : the model proposes that Nor-1 (early), Ver-1 (middle), and OmtA (late) are synthesized on free ribosomes in the cytoplasm, packaged into transport vesicles (6 -8), and transported to vacuoles via the cytoplasm-to-vacuole targeting (Cvt) pathway (6,8). In contrast Vbs localizes in the cytoplasm and in structures thought to be Golgi (29), suggesting it is transported to vacuoles via the classical secretory pathway; VBS is glycolsylated in support of this notion.…”
Section: Methodsmentioning
confidence: 99%
“…We previously observed that early (Nor-1), middle (Ver-1), and late (OmtA) aflatoxin enzymes localize in vesicles and vacuoles in A. parasiticus (6)(7)(8). To determine the functional role of these organelles in aflatoxin synthesis, a vesicle-vacuole fraction (V) was first isolated from A. parasiticus grown for 36 h in aflatoxin-inducing medium (YES) using a high-density sucrose cushion method.…”
Section: Vesicles and Vacuoles Are One Primary Site For The Late Stepmentioning
confidence: 99%
See 2 more Smart Citations